Plant Health Management in the Global South: Challenges and Opportunities$ - Prasanna, B M; Carvajal-Yepes, Monica; Kumar, Lava; Ortega Beltran, Alejandro; Kawarazuka, Nozomi; Liu, Yanyan (Indian Journal of Plant Protection, 2025)
Healthy crops are vital for a healthy planet. However, agri-food systems are increasingly challenged by devastating pests and diseases due to climate change, international trade and travel, and weak phytosanitary systems. Farming communities, especially in the low- and middle-income countries, continue to struggle against existing and emerging insect pests and diseases. Each year, these threats result in 10 to 40 percent losses in major food crops and cost the global economy an estimated US$ 220 billion. Moreover, mycotoxins pose serious threat to the health and wellbeing of consumers, with negative impacts on multiple sectors (agriculture, human health, and trade). Recent analyses show that the greatest losses from pests and diseases are associated with food-deficit regions with fast-growing populations.  The CGIAR Plant Health Initiative (PHI), which started in January 2022, builds on the critical, and often pioneering work of CGIAR and partners on plant health management across diverse crops. To effectively counter some of the major crop pests and diseases, PHI is pursuing a holistic approach that includes: 1) globally coordinated diagnostic and surveillance systems; 2) epidemiological modelling, risk assessment,  forecasting and preparedness for proactive management and containment of plant health threats; 3) implementation of context-sensitive, eco-friendly, gender-responsive and socially inclusive integrated  disease and pest management (IPDM) approaches to reduce the impacts of devastating transboundary  pests and diseases; 4) Integrated mycotoxin management in targeted countries in Africa; and 5) gender and social inclusion in plant health management through regional networks. Despite several success stories where major pests and diseases have been brought to control through integrated approaches, further multi-institutional and multi-disciplinary efforts are necessary. Under PHI, “Plant Health Innovation Platforms” have been established in 9 countries in the Global South; these platforms are serving two purposes: a) integrating innovations from diverse institutions into IPDM packages; and b) participatory engagement of national and international partners, extension personnel, and farming communities to identify/validate specific innovation packages that are cost-effective and scalable.  Plant health management requires stronger interface between the biophysical and social sciences, and empowerment of local communities. Understanding gender and cultural influences, besides heterogeneous  socio-economic impacts of plant health innovations, and intensively promoting farmers’ collective action can aid in bridging the gender gap, and improving adoption of IPDM by resource-constrained farmers.